Family history of cancer and malignant germ cell tumors in children: A report from the Children's Oncology Group - Poynter, Jenny N. (2009)
Family history of testicular cancer is an established risk factor for adult testicular germ cell tumors (GCT). We evaluated the association between family history of cancer and pediatric GCT in a Children's Oncology Group case–control study that included 274 GCT cases (195 female and 79 male) diagnosed <age 15 years and 418 controls frequency matched to cases on sex and age. Family history data were collected through telephone interviews with biological mothers and fathers and unconditional logistic regression was used to evaluate associations with GCT adjusting for potential confounders. A family history of cancer with onset <age 40 years was associated with a reduced risk of GCT among female cases (Odds Ratio (OR) = 0.50, 95% Confidence Interval (CI) 0.28–0.89) and an increased risk among male cases (OR = 2.56, 95% CI 1.02–6.44). Male cases were more likely to report family history of melanoma compared with male controls (OR = 4.65, 95% CI 1.40–15.4). There was an inverse association between family history of ovarian or uterine cancers and GCT in girls (OR = 0.46, 95% CI 0.22–0.96). These sex and cancer site specific associations should be confirmed in additional studies as they may provide clues to the etiology of pediatric GCT.